Hazards in chromatographic bioanalysis method development and applications. (6th November 2016) - Hooshfar, Shirin; Bartlett, Michael G.
Abstract: Bioanalytical methods are employed for the quantitative determination of drugs and their metabolites in biological matrices, in all stages of the drug development process. However, because of the highly complex nature of these matrices there is a wide range of potential biological, chemical and physical hazards that can influence the quality of the data produced by these methods. The present review focuses on the evaluation of the most important and frequent errors that may be encountered during bioanalytical method development/validation and analysis of clinical or preclinical samples mainly using chromatography. Additionally, the most practical ways for avoiding and managing these hazards during routine bioanalysis are presented.